Ergonomic evaluation of a wheelchair transportation securement system. - Soares, Marcelo M.; Jacobs, Karen; Ahmed, Madiha; Campbell-Kyureghyan, Naira; Frost, Karen; Bertocci, Gina (Work)
The Americans with Disabilities Act (ADA) specifies guidelines covering the securement system and environment for wheeled mobility device (WhMD) passengers on the public bus system in the United States, referred to as the wheelchair tiedown and occupant restraint system (WTORS). The misuse or disuse of the WTORS system can be a source of injury for WhMD passengers riding the buses. The purpose of this study was to quantify the risks posed to the bus driver while performing the WTORS procedure using traditional ergonomic analysis methods. Four bus drivers completed the WTORS procedure for a representative passenger seated in three different WhMDs: manual wheelchair (MWC), scooter (SCTR), and power wheelchair (PWC). Potential work-related risks were identified using the four most applicable ergonomic assessment tools: PLIBEL, RULA, REBA, and iLMM. Task evaluation results revealed high levels of risk to be present to drivers during the WTORS procedure. The securement station space design and equipment layout were identified as contributing factors forcing drivers to adopt awkward postures while performing the WTORS task. These risk factors are known contributors to injury and the drivers could opt to improperly secure the passengers to avoid that risk.